Mouse Model Established by Early Renal Transplantation After Skin Allograft Sensitization Mimics Clinical Antibody-Mediated Rejection - Zhao, Daqiang; Liao, Tao; Li, Siwen; Zhang, Yannan; Zheng, Haofeng; Zhou, Jing; Han, Fei; Dong, Yu; Sun, Qiquan (Frontiers in Immunology, 2018)
Antibody-mediated rejection (AMR) is the main barrier to renal graft survival and mouse renal AMR models are important to study this process. Current mouse models are established by priming the recipient to donor skin for over 7 days before kidney transplantation. The robustness of AMR in these cases is too strong to mimic clinical AMR and it is unclear why altering the priming times ranging from 7 to 91 days fails to reduce the AMR potency in these models. In the present study, we found that the donor-recipient combination and skin graft size were determinants of donor-specific antibody (DSA) development patterns after skin transplantation. DSA-IgG was sustained for over 100 days after skin challenge, accounting for an identical AMR robustness upon different skin priming times over 7 days. However, decreasing the skin priming time within 7 days attenuated the robustness of subsequent renal allograft AMR in C3H to Balb/c mice. Four-day skin priming guaranteed that recipients develop acute renal AMR mixed with a high ratio of graft-infiltrating macrophages, renal grafts survived for a mean of 6.4 ± 2.1 days, characterized by typical AMR histological changes, such as glomerulitis, peritubular capillary (PTC) dilation, and capillaritis, deposition of IgG and C3d in PTCs, but less prevalence of microthrombus, whereas the cellular rejection histological change of tubulitis was absent to mild. With this scheme, we also found that the renal AMR model can be developed using common mouse strains such as C57BL/6 and Balb/c, with mean prolonged renal graft survival times of 14.4 ± 5.0 days. Finally, we proved that donor-matched skin challenge after kidney transplantation did not strongly affect DSA development and kidney graft outcome. These findings may facilitate an understanding and establishment of mouse renal allograft AMR models and promote AMR associated studies.